2020
DOI: 10.1136/bmjopen-2020-038718
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and hospitalisation in the Danish Helicopter Emergency Medical Service (HEMS) population from 2014 to 2018: a national population-based study of HEMS triage

Abstract: ObjectiveTo describe characteristics and outcomes for patients where the Danish Helicopter Emergency Medical Service (HEMS) either transported the patient to hospital, treated the patient on scene but did not transport the patient or was dispatched but cancelled en route to the patient (aborted mission), and to assess the field triage by comparing these outcomes.DesignNational population-based study.Setting and participantsHEMS dispatches are undertaken from the five Danish emergency dispatch medical centres a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 19 publications
6
9
0
Order By: Relevance
“…The mean age (71.81 years) and gender ratio (69.8% males) of the patients who participated in our study were shown to be consistent with some previous reports [ 24 ]. The total time from call-to-hospital in our cohort was significantly shorter for males, including call-to-flight time.…”
Section: Discussionsupporting
confidence: 92%
“…The mean age (71.81 years) and gender ratio (69.8% males) of the patients who participated in our study were shown to be consistent with some previous reports [ 24 ]. The total time from call-to-hospital in our cohort was significantly shorter for males, including call-to-flight time.…”
Section: Discussionsupporting
confidence: 92%
“…In 2 recent studies describing patient characteristics and mortality for different HEMS mission types, 3,4 similar findings were reported when analyzing the entire HEMS patient population. 4 Christensen et al 21 described mortality and diagnostic distribution among a cohort of emergency patients brought to the hospital by ambulance during the period 2007 to 2014 in the North Denmark region. The study showed mortality at day 1 and day 30 of 1.8% and 4.7%, respectively.…”
Section: Discussionsupporting
confidence: 58%
“…Di Rocco et al looked at a population with a mean age of 51, and 61% were male [ 7 ]. Alstrup et al report two separate studies where the population had a median age of 60 and males composed 71% in one study and 64% in the second study [ 8 , 9 ]. The pediatric patient population had a median age of two in this study, with 60% male participants.…”
Section: Discussionmentioning
confidence: 99%
“…This study examines a general view of patients transported by helicopter, while other studies, such as by Di Rocco et al, have limited patient demographics. Di Rocco et al gathered information on flight distances and flight interventions, which this study did not [ 8 ]. This study only looked at the time to call for transport at the sending facility and the patient's length of stay at the sending facility before transport arrives.…”
Section: Discussionmentioning
confidence: 99%